Factors associated with health related quality of life after a hip or knee total replacement, according to a gender approach - Sergio R. López Alonso; Antonio Olry de Labry Lima; Carmen M. Martínez Sánchez; Félix Navarro Casado; Ana B. Romero Cañadillas; Josefina González Rojo (Fundación para el Desarrollo de la Enfermería, 2010)
Objective: To identify the factors associated with Health Related Quality of Life (HRQL), and Symptoms and Physical Functional Disability (S&PFD) after a Hip or Knee Total Replacement, according to a gender approach. A longitudinal cohort study design is performed at "La Merced" (Osuna. Sevilla) and "Torrecárdenas" (Almería) Hospitals, via telephone interview since October 2004 to November 2006. The study included all people who underwent a hip or knee total replacement. The dependent variables were HRQL and S&PFD, both measured via short versions of the COOP/WONCA and WOMAC questionnaires.Results: 311 people were included, who were mostly women (82,63%) and 70 years old (average). The hip and knee replacement obtained an statistically significant improvement on HRQL (20,5%) and S&PFD (28,2%), with no gender difference. Five variables were associated to HRQL for Women: HRQL previous to surgery, hospital, local infection as a complication, autonomy for daily living, and marital status. All of them were associated to men, except the last two ones. About S&PFD, six variables were associated for women: HRQL and S&PFD previous to surgery, hospital, local infection as a complication, body mass index and marital status. All of them were associated to men, except the last two ones.Factors associated to improve on HRQL and S&PFD in male population are few, though they find a great explanation of the improvement. Different situation arise on female population because more factors obtained a substantially inferior explanation.